"Ibero-American participation, world exhibitions, and the long nineteenth century: a historiographical overview". Issue 3 (1st September 2020) - Boone, M. Elizabeth
ABSTRACT: Walter Benjamin (1892–1940), while working on the Arcades Project during the final years of his life, produced two extended outlines – he called them Exposés – for "Paris, the Capital of the Nineteenth Century." The third part was titled "Grandville, or the World Exhibitions." An important source for scholars working on world's fairs and international exhibitions, Benjamin's Exposés provide a place from which to explore a broad number of themes related to the development of nineteenth-century modernity and consumer capitalism, from advertising and fashion to entertainment and representation. Spectacular environments that purportedly reproduced the world, international exhibitions were fabulously popular in the nineteenth and early twentieth centuries. They continue to be so today.